Internal Control Perspective Based on Islamic Worldview - Mohamad Djasuli (JAFFA, 2021)
The purpose of the study is to explore and explain the perspective of internal control in the Islamic worldview. This research uses a descriptive qualitative method with Al-Quran and Al-Hadith and related references as research sources. Although the internal control framework model used is based on the COSO framework created in 1985, it has been implemented by Muslim leaders since the era of the Prophet Muhammad until the Abbasid era. The five elements of internal control established by the COSO framework include the control environment, risk assessment, control activities, information and communication, and monitoring. Indicators of control environment elements, researchers recommend adding spirituality and religiosity. The basic element of internal control is the control environment. If the control environment is functioning properly, it will minimize risk, control activities will be carried out simply, information and communication will run smoothly and internal control monitoring can be carried out regularly.